Imitation modeling of ice dams (case study of Tom’ River, Western Siberia) - V. A. Zemtsov; D. A. Vershinin; N. G. Inishev (Лëд и снег)
The factors of ice jam formations in the lower flow of the Tom River (Siberia) are investigated. A length of the main channel under investigation is about 120 km. Approaches to solution of the problem of the jam formation control and, as a consequence, the jam induced floods are considered on the basis of the imitative computer modeling of stream dynamics and ice jams. The simulation makes it possible to analyze different scenarios of initial forcing and to predict reactions of the river bed system to the effects. On the basis of 1D models developed in the HEC-RAS 4.0 modeling system for the Tom River at the city of Tomsk we investigated a possibility of the ice jam localization, probability of which at different parts of river flow varies in time according to change of the river water discharge, stream hydraulics, and ice cover thickness. The 2D hydrodynamic model of the Tom River channel system in the SMS 9.2 modeling system has been developed. It allows simulating effects of ice jams located in different sections of the river flow on the run-off redistribution between the main channel and other river branches. It makes possible to estimate hazards and risks of ice jam floods and probable effects of ice jams on formation of the river channel system. As a result it becomes possible to regulate the safe spring ice transit through populated areas.Analysis of factors of the ice jam formations has demonstrated that due to increasing anthropogenic influence changes of hydro-meteorological and geomorphologic conditions lead to more frequent occurrence of jam floods for the last 25 years as compared to previous 40-year period. The imitative computer models are proposed to be used for planning anti-jam measures since they make possible to create a whole system of the channel structure, a relief of channel and floodplain, a flow velocity field including dangerous hydrologic processes. Similar system would allow predicting both consequences of local anthropogenic influences and their synergic effects. A change of a pressure head along the river course under fixed water discharges at initial hydraulic section can be calculated with the 1D flow model so that to determine places of the most probable localization of the ice jams. A computer simulation of jams in the river channel system with use of preassigned increased roughness coefficients allows quantitative estimating of the runoff redistribution within the channel system under certain scenarios of a spring flood in the jam-dangerous parts of branching river channels. It is important to preserve such branches, and they should be cut by any dam from a main channel.